Synthesis and characterization of multiwalled carbon nanotubes-silver nanoparticles reinforced polyvinyl alcohol nanocomposites (PVA/MWNT-AgNP) as high permittivity materials / Yusliza Yusof - Yusliza , Yusof (2019)
This study about tailoring high dielectric permittivity of multiwalled carbon nanotubes-silver nanoparticles reinforced polyvinyl alcohol nanocomposites (PVA/MWNT-AgNP). The combination of MWNT and silver nanoparticles (AgNP) is an alternative way to yield high permittivity () polymer composites that is favorable for electrical/electronic industry with attractive features. The hybrid fillers of MWNT-AgNP are produced via a single step route of chemical reduction method prior to the solution mixing process with PVA matrix. The characterization of the as-synthesized MWNT-AgNP was done using Raman spectroscopy, Fourier transform infrared (FTIR), field emission scanning microscopy (FESEM) and transmission electron microscopy (TEM). The properties of PVA/MWNT-AgNP nanocomposites with different AgNP contents are characterized in terms of morphology, structure properties, thermal stability, electrical and dielectric properties. Main finding shows that the inclusion of MWNT-AgNP in PVA matrix not only improves the electrical conductivity, but at the same time triggers a significant increase in dielectric permittivity of the nanocomposites. Impedance spectroscopy analysis shows high dependence of ac-conductivity,ac and dielectric permittivity, over frequency within 100 Hz to 1MHz. The maximum value of ac is 4.0x10-5 S/m and  is about 600 for the nanocomposites containing 1.0 wt% of AgNP. FESEM analysis reveals random distribution of MWNT embedded in the matrix with high irregular interfaces can act as the conductive bridges when in contact together with AgNP. The average particles size of AgNP was found in the range of 17nm to 55nm. In addition, UV-vis analysis correlates other results with the absorption of visible light to the occurrence of charge transfer process between the fillers and the matrix. Vector network analyzer (VNA) further evaluates electromagnetic properties of the nanocomposites at a higher frequency of 8 to 12 GHz (X-band). In this part, the  value of the nanocomposite containing 1.0 wt% of AgNP remains stable at 25 over the X-band frequency, while the permeability μ, is approaching close to 0.5 due to low susceptibility of the nanocomposites with magnetic field. Both properties influence the ability of these nanocomposites to reduce the amount of transmitted electromagnetic waves. This is attributed to a higher wave absorption than the reflection behavior of the nanocomposite with the increased of AgNP-dielectric interfaces. Overall, PVA/MWNT-AgNP nanocomposite is promising material to impart high permittivity with good electromagnetic absorption. Thus, it can offer great potentials in electrical applications such as high-energy storage and dielectric-wave absorbance materials at high frequency.